Retained gastrostomy bumper resulting in esophageal fistula and spinal osteomyelitis - Ariela Zenilman; Jennifer DeFazio; Cornelia Griggs; Joseph Picoraro; Erica M. Fallon; William Middlesworth (Elsevier, 2020)
Background: We report a case of spinal osteomyelitis and fistulous tract between the esophagus and prevertebral soft tissues secondary to an esophageal foreign body. This resulted from a retained gastrostomy bumper that broke on removal of the tube seven years earlier. Case presentation: A 9-year-old male with Troyer Syndrome and developmental delay presented to his pediatrician with the refusal to bear weight and new onset torticollis, and was referred to our institution for further evaluation. He was admitted for further workup due to concern for a neurological process. Imaging revealed osteomyelitis of T3/T4 and inflammatory changes in the posterior mediastinum with possible communication with the esophagus. His gastrostomy tube (GT) was converted to a gastrojejunal tube (GJT) for post-pyloric feeding. He acutely worsened after this procedure, and further radiographic imaging revealed a retained foreign body in the esophagus. An upper endoscopy was subsequently performed with snare removal of the object, identified as the bumper of a previous gastrostomy tube. This esophageal foreign body caused esophageal erosion leading to creation of a fistulous tract with nidus for infection spread posteriorly. The patient underwent prolonged treatment for the infection, with improvement in his presenting symptoms, and eventually resumed gastrostomy feeding. Conclusion: Retained foreign body following gastrostomy removal, while typically does not warrant further investigation, may present with significant sequelae if retained especially in children with developmental delay and feeding difficulties.